Experience Report on Innovation in E-commerce: Research and Design of an Assisted Remote Sales Application - Silva, Pedro Victor de Sousa; de Souza, Anna Julia Abreu Lima; Teixeira, Ingrid Monteiro (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
An e-commerce system aims to support buying and selling over the internet. Despite the strong appeal of self-service provided by e-commerce, assisted sales (both in-person and remotely) and sales influenced by social networks have proven to be strategic for many retail companies. This paper presents an experience report from a designers team developing new functionalities for a remote sales application, as part of a partnership program between a university and a Brazilian company VTEX specialized in administrative and sales solutions for e-commerce businesses. This application was initially intended for sales in physical store settings. However, with the growing change in consumer behavior, VTEX identified the opportunity to invest in the remote sales scenario, leveraging its existing physical store sales solution. To develop the new functionalities, various Human-Computer Interaction (HCI) and User Experience (UX) techniques were applied within the Double Diamond design process, such as the CSD matrix, field research, benchmarking, support ticket analysis, interaction diagrams with MoLIC, and high-fidelity prototypes. In this paper, we report how each technique was applied and present the results obtained from them. The research findings revealed numerous opportunities for the design team to capitalize on when modeling the solution. Some lessons learned from this case study included: placing significant emphasis on the briefing document, objectively describing the problems to be addressed by the project team; utilizing the company’s internal tickets as a research source about the users; creating opportunity banks based on research findings to help demonstrate the value of the research to stakeholders and serve as a knowledgesharing tool among teams; and developing solutions that leverage the existing structures of the current solution can assist the product team in defending the ideas of the developed products. Finally, the collaboration between industry and academia in this experience report proved to be highly beneficial.